6x+7(6x-1)=377

Simple and best practice solution for 6x+7(6x-1)=377 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+7(6x-1)=377 equation:



6x+7(6x-1)=377
We move all terms to the left:
6x+7(6x-1)-(377)=0
We multiply parentheses
6x+42x-7-377=0
We add all the numbers together, and all the variables
48x-384=0
We move all terms containing x to the left, all other terms to the right
48x=384
x=384/48
x=8

See similar equations:

| 2(4x-3=5x+18 | | 7d-12d+3d=15 | | 91=7(n-6) | | 7+t=35 | | │x-7│=5 | | ?x3+8=23 | | 25-0.6*x=52 | | 6y-5=4y+3 | | 40x+22.6995x=1520.5 | | 13=23-x | | 40x+15.133(1.5x)=1520.5 | | x-7=|5-3x| | |  2x-6=-8 | | 1/12x+1/3+2^(1/6x+2/9)=1/3(x+2) | | 50+2.5x=75 | | 1+4x=180 | | 3x+4=30x+85 | | F(x)=4^4-1 | | 3x+4=(6x+5)+60 | | |x-2|=2x+4 | | |x-+2|=|2x-2| | | 5+b=104 | | 5x-8=27x | | 9y+3=8y+10 | | 5(5x+66)=3(x+88) | | 15−3y=-8y+30 | | -12u=-15u+27 | | -4w-2=-5w | | x=25/24 | | 10x-9=9x=-4 | | x=25/25 | | 10x-9=9x=4 |

Equations solver categories